2013
DOI: 10.1097/inf.0b013e31828bbe68
|View full text |Cite
|
Sign up to set email alerts
|

Undervaccination of Perinatally HIV-infected and HIV-exposed Uninfected Children in Latin America and the Caribbean

Abstract: Background Perinatally HIV-infected children (PHIV) may be at risk of undervaccination. Vaccination coverage rates among PHIV and HIV-exposed uninfected children (HEU) in Latin America and the Caribbean were compared. Methods All PHIV and HEU children born from 2002–2007 that were enrolled in a multi-site observational study conducted in Latin America and the Caribbean were included in this analysis. Children were classified as up to date (UTD) if they had received the recommended number of doses of each vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
5
1
1
Order By: Relevance
“…Other studies carried out in Africa found that children born to HIV-infected mothers had lower immunization coverage than those born to HIV-negative mothers, 14,18 and even that HIV seropositive children were more likely to be incompletely vaccinated than their seronegative pairs. 12,19 To this regard, HIV seropositive children may be more likely to be hospitalized than other children and miss appointments at times when their immune system is suppressed. It is also possible that doctors and parents may tend not to immunize HIV positive children to avoid complications from vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies carried out in Africa found that children born to HIV-infected mothers had lower immunization coverage than those born to HIV-negative mothers, 14,18 and even that HIV seropositive children were more likely to be incompletely vaccinated than their seronegative pairs. 12,19 To this regard, HIV seropositive children may be more likely to be hospitalized than other children and miss appointments at times when their immune system is suppressed. It is also possible that doctors and parents may tend not to immunize HIV positive children to avoid complications from vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…This risk may be compounded by missed opportunities for recommended immunizations in PHIV, despite specific immunization guidelines for HIV-infected children (1, 2, 3), perhaps because healthcare providers may be unaware of the recommendations or concerned that vaccination poses greater risks in this population. In a previous study of Latin American and Caribbean PHIV and HEU children enrolled in the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) International Site Development Initiative (NISDI), the rates of complete vaccination of children at age 24 months varied from 43.5% to 74.5% in the PHIV group and 74.2% to 94.2% in the HEU group with PHIV children being significantly less likely to be vaccinated for all vaccines examined (4).…”
Section: Introductionmentioning
confidence: 92%
“…31 Clinician hesitancy to provide live attenuated vaccines (measles and yellow fever vaccines) to symptomatic children might explain low rates of these 2 vaccines, however, all children should have received the DTPPH series in the first 8-12 months of life. Suboptimal vaccination completion among HIV-infected children has been reported in other countries.…”
Section: Trends In Patient Characteristics At Art Initiation Over Timementioning
confidence: 99%